Jätteträd : inventering, bevaring, skötsel samt rekrytering - Holst, Christian (SLU/Southern Swedish Forest Research Centre, 2008)
During the summer of 2007 I was employed by Högestad Christinehofs Förvaltning AB. My main task was to make an inventory of giant trees at the estate. Högestad and Christinehof,which with their total possession of 13 000 ha of land is the biggest estate in Scania. A giant tree is a tree with a diameter in breast height more then 1 meter. Trees of these dimensions are registered by Swedish authorities. Landowners with a giant tree on their property can receive a subsidy for cutting trees that are in competition with the giant tree.(Levenskog, 2007) Giant trees are important for biodiversity in the landscape and there are important habitats for different insects, birds, bats, lichens and funguses. (Levenskog, 2007) The inventory was divided into three different parts. The first part of the work was to study aerial orto- photos. The second part was to make interviews with people who were working at the estate and might knew were to find giant trees. The last part was to make a field inventory, searching for giant trees. The inventory resulted in that 433 giant trees were located. Of these 204 were located on forestland. Oak (47 %) and beech (37 %) were the main dominating species. There were only a few very big trees, most of the trees had a diameter just over 1 meter. Around 30 % of the trees had a diameter over 120 cm and only 5 % of the trees had a diameter over 150 cm. The biggest tree was a beech with a diameter of 227 cm, it turned out to be the second biggest beech in Sweden. (Hultgren et al. 2007) It was suggested that a giant tree on average need 571 m² to develop well. In this area a protecting zone of 5 meter around the border of the crown was included. It is good to have a management plan for each and every giant tree. A management plan can booth help the landowner to know what actions that have to be taken to protect the tree and show to others what actions that are taken to protect the tree. The most important variable when a single tree shall be left for conservation is the trees net value.